Respiratory manifestations of gastro-oesophageal reflux in children. Issue 3 (7th September 2017) - de Benedictis, Fernando Maria; Bush, Andrew
Abstract : Gastro-oesophageal reflux disease (GORD) is a complex problem in children. Suspected respiratory manifestations of GORD, such as asthma, chronic cough and laryngitis, are commonly encountered in the paediatric practice, but continue to be entities with more questions than answers. The accuracy of diagnostic tests (ie, pH or pH-impedance monitoring, laryngoscopy, endoscopy) for patients with suspected extraoesophageal manifestations of GORD is suboptimal and therefore whether there is a causal relationship between these conditions remains largely undetermined. An empiric trial of proton pump inhibitors can help individual children with undiagnosed respiratory symptoms and suspicion of GORD, but the response to therapy is unpredictable, and in any case what may be being observed is spontaneous improvement. Furthermore, the safety of these agents has been called into question. Poor response to antireflux therapy is an important trigger to search for non-gastro-oesophageal reflux causes for patients' symptoms. Evidence for the assessment of children with suspected extraoesophageal manifestations of GORD is scanty and longitudinal studies with long-term follow-up are urgently required.